Family-based collaborative eco-literacy model for sustainable city - Sudar Itafarida; Eduardus Bimo Aksono Herupradoto; Usma Nur Dian Rosyidah; Erlita Rusnaningtias (Masyarakat, Kebudayaan dan Politik, 2019)
The process of adaptation and adoption of modern values by multicultural urban communities raises various problems, especially those related to the environment. In Surabaya and Sidoarjo, even though the Surabaya City Government and the Regional Government of Sidoarjo have carried out various environmental programs, the demands of a fast and practical modern lifestyle create egocentric and anthropocentric attitudes. Urban communities must take on the continuous socialization of ecocentric behavior that adopts modern values but must also maintain the value of local wisdom to support the realization of sustainable city. The family-based collaborative eco-literacy model is needed as a strategy to develop green living cultural values that can be practiced by all levels of society in various regions with different characteristics in both cities. This model directly touches the family as the main place to cultivate ecocentric mindset and behavior. Another consideration is that there is few government policies related to environment that directly target the family. This study illustrates how the family-based collaborative ecoliteracy model was applied to families in Surabaya and Sidoarjo and explains how the model has moved the attitudes and behavior of these families to those in line with ecocentric principles. By using a qualitative-descriptive approach, this model was applied to 16 families selected according to participant criteria. The subsequent changes in behavior were observed over a period of six months. The results of the application of the model show that each individual in the family collaborates and strengthens due to collective competence, which is an ecocentric value. Based on the orientation of green living values in eleven sustainable urban components, it can be concluded that almost all green city programs carried out by the government are intended to realize Surabaya and Sidoarjo as sustainable cities.